Quantitative PCCT imaging in differentiating adrenal adenomas from metastases: diagnostic performance and its clinical applications - Haag, Florian; Emmrich, Shanice S.; Hertel, Alexander; Rink, Johann; Vellala, Abhinay K.; Komlen, Sara; Nörenberg, Dominik; Schönberg, Stefan; Froelich, Matthias F. (Abdominal radiology, 2025)
To evaluate the potential of Photon counting CT (PCCT) -derived iodine densities and Virtual-Non-Contrast (VNC) reconstructions for the differentiation between adrenal adenomas and adrenal metastases.